2020
DOI: 10.1111/bjd.19377
|View full text |Cite
|
Sign up to set email alerts
|

Most chilblains observed during the COVID‐19 outbreak occur in patients who are negative for COVID‐19 on polymerase chain reaction and serology testing*

Abstract: Summary Background Acral lesions, mainly chilblains, are the most frequently reported cutaneous lesions associated with COVID‐19. In more than 80% of patients tested, nasopharyngeal swabs were negative on reverse transcription polymerase chain reaction (RT‐PCR) for SARS‐CoV‐2 when performed, and serology was generally not performed. Methods A national survey was launched on 30 March 2020 by the French Society of Dermatology asking physicians to report cases of skin manifestations in patients with suspected or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
84
1
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 34 publications
5
84
1
7
Order By: Relevance
“…( Baeck et al, 2020c , Ko et al, 2020 ). Conversely, RT-PCR and anti-SARS-CoV-2 serology were mostly negative ( Herman et al, 2020 , Baeck et al, 2020a , Caselli et al, 2020 , El Hachem et al, 2020 , Neri et al, 2020 , Roca-Ginés et al, 2020 , Rouanet et al, 2020 , Rizzoli et al, 2020 , Mahieu et al, 2020 , García-Legaz Martínez et al, 2020 , Garcia-Lara et al, 2020 , Freeman et al, 2020b , Colonna et al, 2020 , Le Cleach et al, 2020 , Lesort et al, 2020 , Stavert et al, 2020 , Denina et al, 2020 ). Negative RT-PCR on nasopharyngeal swabs could suggest that chilblains are a late symptom of COVID-19.…”
mentioning
confidence: 99%
“…( Baeck et al, 2020c , Ko et al, 2020 ). Conversely, RT-PCR and anti-SARS-CoV-2 serology were mostly negative ( Herman et al, 2020 , Baeck et al, 2020a , Caselli et al, 2020 , El Hachem et al, 2020 , Neri et al, 2020 , Roca-Ginés et al, 2020 , Rouanet et al, 2020 , Rizzoli et al, 2020 , Mahieu et al, 2020 , García-Legaz Martínez et al, 2020 , Garcia-Lara et al, 2020 , Freeman et al, 2020b , Colonna et al, 2020 , Le Cleach et al, 2020 , Lesort et al, 2020 , Stavert et al, 2020 , Denina et al, 2020 ). Negative RT-PCR on nasopharyngeal swabs could suggest that chilblains are a late symptom of COVID-19.…”
mentioning
confidence: 99%
“…However, most of these acral chilblain lesions showed negative COVID-19 PCR and serology and they resolved on their own. 3,4 With further pathology, immunohistochemistry and electron microscopy studies, [5][6][7][8] This pathophysiology was also shown to be similar to that occurring in the lung. 5 The retiform-like purpuric lesions are an advanced form of the coagulopathies with thrombi in larger vessels which could lead to strokes, pulmonary emboli, and an elevated D-Dimer with a poorer prognosis.…”
mentioning
confidence: 72%
“…They hypothesized that the situation could be due to the media stating that chilblains were caused by SARS-CoV-2 infection and leading to a higher rate of consultation or the lockdown leading to more inactivity and long periods at home barefoot on a cold floor. 1 We do not agree with this explanation. We recently published cases of chilblains enrolled during the COVID-19 pandemic.…”
mentioning
confidence: 77%
“…Negative tests for SARS-CoV-2 infection do not rule out its responsibility for chilblains DOI: 10.1111/bjd.19483 DEAR EDITOR, We read with great interest the report of Le Cleach et al discussing chilblains as a manifestation of the COVID-19 pandemic. 1 They reported 311 patients with acral lesions occurring during the COVID-19 lockdown in France. The most frequent clinical presentation of these acral lesions was typical chilblains.…”
mentioning
confidence: 99%